Non-holomorphic modular A4 symmetric scotogenic model - Takaaki Nomura; Hiroshi Okada; Oleg Popov (Physics Letters B)
The present work extends scotogenic and its modular A4 variation a step forward and demonstrates scotogenic modular A4 non-supersymmetric realization. To achieve this non-holomorphic modular symmetries come to rescue. Advantage of the current construction is the compactness of the model content and absence of the supersymmetric fields. Neutrino mass is generated through a canonical scotogenic mechanism. The allowed values of the VEV of the τ modulus are τ≃w and Im[τ]≈2. The non-holomorphic modular A4 symmetry leads to correlations among the neutrino observables.